(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2018)
Article is about the problem of strangeness and its aspects in the life of a literary hero. Oscar Matzerath, the hero of the novel „Tin drum” of Günter Grass, constantly seeking his identity, is alien to both the environment and himself. The novel shows that the feeling of strangeness can not be completely eliminated, and the battle for the approval of the environment can be won only by fully accepting ourselves.